Vibration-synchronized magnetic resonance imaging for the detection of myocardial elasticity changes - Elgeti, Thomas; Tzschaetzsch, Heiko; Hirsch, Sebastian; Krefting, Dagmar; Klatt, Dieter; Niendorf, Thoralf; Braun, Juergen; Sack, Ingolf (Magnetic Resonance in Medicine, 2012)
Vibration synchronized magnetic resonance imaging of harmonically oscillating tissue interfaces is proposed for cardiac magnetic resonance elastography. The new approach exploits cardiac triggered cine imaging synchronized with extrinsic harmonic stimulation (f = 22.83 Hz) to display oscillatory tissue deformations in magnitude images. Oscillations are analyzed by intensity threshold-based image processing to track wave amplitude variations over the cardiac cycle. In agreement to literature data, results in 10 volunteers showed that endocardial wave amplitudes during systole (0.13 ± 0.07 mm) were significantly lower than during diastole (0.34 ± 0.14 mm, P < 0.001). Wave amplitudes were found to decrease 117 ± 40 ms before myocardial contraction and to increase 75 ± 31 ms before myocardial relaxation. Vibration synchronized magnetic resonance imaging improves the temporal resolution of magnetic resonance elastography as it overcomes the use of extra motion encoding gradients, is less sensitive to susceptibility artifacts, and does not suffer from dynamic range constraints frequently encountered in phase-based magnetic resonance elastography. © 2011 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-08-03
Keywords: cardiac elastography; heart contraction; MRE; myocardial relaxation; shear modulus; shear waves; time harmonic vibrations